Automatic Wheeze Detection in Lung Sounds - Kulkarni, KS; Chorage, SS (International Journal of Computer Sciences and Engineering, 2025)
Lung disease is mainly characterized by the variations that occur in breathing sound of human being. The variations are characterized as wheezes, crackles, etc. Wheezes are one of the most important adventitious sounds in pulmonary system. They are observed in asthma, chronic obstructive pulmonary disease (COPD) and bronchitis. The current method of detecting a lung disease for example asthma involves usage of spirometers and stethoscope. The results with these techniques are not efficient. A wheezing detection system may help physicians to monitor patients over the long-term. This technique involves on board capture and processing methodology. This paper involves the system for breath sound acquisition and real time pre-processing and detection of abnormality in lung sounds using DSP processor. The aim of the system is to design and develop portable device for acquisition and detection of abnormality in lung sounds.